2002
DOI: 10.1021/es020639y
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Personal Particulate Organic and Mass Sampler

Abstract: Accurate measurement of personal exposure to particulate matter and its constituents requires samplers that are accurate, compact, lightweight, inexpensive, and convenient to use. The Personal Particulate Organic and Mass Sampler (PPOMS) has been developed to meet these criteria. The PPOMS uses activated carbon-impregnated foam as a combined 2.5-µm size-selective inlet and denuder for assessment of fine particle mass and organic carbon. Proof of the PPOMS concept has been established by comparing mass and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The average nighttime FP-OC1 was 1.15 µg C/m 3 , compared to an average IOGAPS-OC1 of 0.37 µg C/m 3 . Our findings are consistent with results reported by Pang et al (2002c). They used two denuder-based samplers and a FP sampler to collect indoor PM 2.5 samples in May 2001 in Seattle, WA.…”
Section: Diurnal and Seasonal Variations Of Oc Determined By The Iogasupporting
confidence: 92%
See 1 more Smart Citation
“…The average nighttime FP-OC1 was 1.15 µg C/m 3 , compared to an average IOGAPS-OC1 of 0.37 µg C/m 3 . Our findings are consistent with results reported by Pang et al (2002c). They used two denuder-based samplers and a FP sampler to collect indoor PM 2.5 samples in May 2001 in Seattle, WA.…”
Section: Diurnal and Seasonal Variations Of Oc Determined By The Iogasupporting
confidence: 92%
“…These have included the Particle Concentrator-Brigham Young University Organic Sampling System (PC-BOSS; Eatough et al 2001) and the integrated organic gas and particle sampler (IOGAPS; Gundel et al 1995;Lewtas et al 2001;Pang et al 2002c). The IOGAPS, which was used in this study, collects the particles (i.e., PM 2.5 ) by a quartz filter placed downstream of a XAD-resin-coated denuder that functions to remove gas-phase organics.…”
Section: Introductionmentioning
confidence: 99%
“…19,55 It has been reported that the indoor proportion of outdoor particles can vary from 5% to Ͼ90% depending on the ventilation status of a building. 55 For residences likely to be similar to those in this study (i.e., continuous central air conditioning and a standard furnace filter), Riley et al 54 calculated indoor proportion of outdoor particles of 44% for sulfate and 38% for EC. This suggests that although there appears to be some difference between these two particle-bound constituents, which may be because of differences in their size, it is not large.…”
Section: Sources Of Personal Exposure To Pm 25mentioning
confidence: 99%
“…38 In the case of OC sampling for personal exposure measurements positive artifacts are also known to be problematic. 54 It was believed that these negative and/or positive artifacts would significantly bias personal exposure measurements, because the particle load on sampled filters was very low. However, in this study, these sources of sampling bias could not be investigated, because collocated, unbiased measurements were not available.…”
Section: Quality Assurancementioning
confidence: 99%
“…21 Additional fixed 4-L/min HI 2.5 samplers were collocated both outdoors and indoors to measure particulate organic (OC) and elemental (EC) carbon on quartz filters via thermal optical transmittance using a modified version of the National Institute of Occupational Safety and Health method. 26,27 The particle light absorption coefficient (b ap ) on the Teflon filters was also measured using an integrating plate method. 28 -30 It is important to note that personal quartz filter samples were collected but suffered from various analysis problems, mainly a large positive sampling artifact for OC.…”
Section: Sampling and Analysismentioning
confidence: 99%